Design and protocol of Estrogenic Regulation of Muscle Apoptosis (ERMA) study with 47 to 55-year-old women's cohort: novel results show menopause-related differences in blood count. Issue 9 (September 2018) - Kovanen, Vuokko; Aukee, Pauliina; Kokko, Katja; Finni, Taija; Tarkka, Ina M.; Tammelin, Tuija; Kujala, Urho M.; Sipilä, Sarianna; Laakkonen, Eija K.
Abstract: Objective: The multidisciplinary Estrogenic Regulation of Muscle Apoptosis (ERMA) study was designed to reveal how hormonal differences over the menopausal stages affect the physiological and psychological functioning of middle-aged women. This paper describes the protocol and nonrespondent analysis of ERMA and novel findings on menopausal differences in blood count variables and their association with female sex hormones. Methods: Women aged 47 to 55 years were assigned to pre, early peri, late peri, and postmenopausal groups based on follicle-stimulating hormone (FSH) and bleeding diary. Multivariate linear regression models were constructed to estimate the association of 17β-estradiol (E2 ) and FSH with the blood count variables. Results: In all, 3, 064 women returned the prequestionnaire (ERMA phase one), 1, 393 donated blood samples and were assigned to the relevant menopausal group (phase two), and 914 completed phase three, which included physiological and psychological measurements. Nonrespondents were more likely than respondents to be obese, whereas the menopausal groups showed no mean differences in body mass index. Blood count variables, while being within clinical reference values, showed significant differences between groups. E2 and FSH were associated with the white blood cell (WBC) count and neutrophil-to-lymphocyte ratio. Conclusions: The ERMA study was successful in recruiting and characterizing the menopausal status of a cohort sample of middle-aged women. The significant group differences found in the blood count variables and their associations with E2 and FSH verifies menopause-associated changes in WBC composition potentially being an early sign of low-grade inflammation that may develop later in life. Abstract : Supplemental Digital Content is available in the text